2012
DOI: 10.1094/pdis-05-12-0485-pdn
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Phoma macdonaldii, the Causal Agent of Sunflower Black Stem Disease, in Sunflower Fields in China

Abstract: Phoma macdonaldii Boerma is the pathogen of sunflower black stem disease, causing dark black, oval to long lesions on stems of sunflower plants. Infection during early growth stages can reduce yield by 10 to 30% (3). This fungal disease is distributed mainly in North and South America and Europe. In China, the first case was reported in Xinjiang in 2008 (1), and was believed to be introduced as a result of hybrid sunflower seeds being imported from abroad. The Chinese government included this fungus into its q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Black stem is a quarantine disease of sunflower in China and was first reported in the Ili valley of Xinjiang Uygur Region in 2008 (Chen et al, 2008). During 2010 and 2011, 185 diseased samples were collected from 37 commercial farms or individual households in Xinjiang, Inner Mongolia, Ningxia, Hebei and Beijing (Wu et al, 2012) and 105 samples identified as P. macdonaldii positive were from Xinjiang, suggesting that this disease had not spread to other areas since its first discovery in Xinjiang Uygur region (Wu et al, 2012). Chinese Entry-Exit Inspection and Quarantine Bureau has imposed inspection of imported sunflower seeds for P. macdonaldii and the first intercept record was reported in 2011 (Luo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Black stem is a quarantine disease of sunflower in China and was first reported in the Ili valley of Xinjiang Uygur Region in 2008 (Chen et al, 2008). During 2010 and 2011, 185 diseased samples were collected from 37 commercial farms or individual households in Xinjiang, Inner Mongolia, Ningxia, Hebei and Beijing (Wu et al, 2012) and 105 samples identified as P. macdonaldii positive were from Xinjiang, suggesting that this disease had not spread to other areas since its first discovery in Xinjiang Uygur region (Wu et al, 2012). Chinese Entry-Exit Inspection and Quarantine Bureau has imposed inspection of imported sunflower seeds for P. macdonaldii and the first intercept record was reported in 2011 (Luo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is the most common stem disease of sunflower in Russia and worldwide (McDonald, 1964;Boerema et al, 1981;Acimovic, 1984;Donald et al, 1987;Maric et al, 1988;Sackston, 1992;Chandreshekar, 1993;Peres, Lefol, 1996;Gulya et al, 1997). In Australia (Chandrashekar, 1993) and China (Wu et al, 2012) the Phoma stem canker causal agent, P. lindquistii, is of quarantine significance. In Russia this fungus is widespread in all sunflower producing regions, such as Krasnodar territory (Borodin, Kotlyarova 2006;Saukova et al, 2014), Tambov province (Vypritskaya et al, 2010), Volgograd province (Saukova et al, 2018), Belgorod province, Central Black Earth region, and North Caucasus (Yakutkin, 2001;2005).…”
Section: Introductionmentioning
confidence: 99%